2013
DOI: 10.1080/00207721.2013.822128
|View full text |Cite
|
Sign up to set email alerts
|

A new lot inspection procedure based on exponentially weighted moving average

Abstract: In this manuscript a new variable sampling plan based on the exponentially weighted moving average (EWMA) statistic is proposed assuming that the quality characteristic follows the normal distribution. The plans are proposed when the standard deviation of the normal distribution is known or unknown. The plan parameters for both cases are determined such that the given producer's risk and consumer's risk are satisfied. The proposed plan includes the ordinary variable single sampling plan as a special case and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 17 publications
0
35
0
Order By: Relevance
“…This problem was solved in Klufa (2008), the exact solution is in Kaspříková (2012) -LTPDvar is an add-on package to the R software (see R Development Core Team 2011). Similar problems are solved in Chen and Chou (2001), Kaspříková and Klufa (2015), Wilrich (2012), Ho et al (2012), Yen et al (2014), Klufa (2015), Aslam et al (2015), Wang and Lo (2015), Balamurali et al (2014).…”
mentioning
confidence: 78%
“…This problem was solved in Klufa (2008), the exact solution is in Kaspříková (2012) -LTPDvar is an add-on package to the R software (see R Development Core Team 2011). Similar problems are solved in Chen and Chou (2001), Kaspříková and Klufa (2015), Wilrich (2012), Ho et al (2012), Yen et al (2014), Klufa (2015), Aslam et al (2015), Wang and Lo (2015), Balamurali et al (2014).…”
mentioning
confidence: 78%
“…The exact plans, using the non-central t distribution in calculation of the operating characteristic Johnson and Welch (1940), have been reported in Klufa (2010) and Kaspříková (2011) -the LTPDvar is an add-on package to the R software (R Development Core Team 2008). Similar problems are solved in Klufa (1997Klufa ( , 2008, Chen and Chou (2001), Kaspříková andKlufa (2011), Wilrich (2012), Aslam et al (2015).…”
Section: Doi: 1017221/186/2014-agriceconmentioning
confidence: 91%
“…For a process with linear profiles, [16] provided a single variable sampling plan based on EWMA model using the yield index . In the literature Aslam et al [15] and Wang [16] suggested that a sampling plan based on EWMA yield index for a normal process and a process with linear profiles has more flexibility and economy than the single sampling plan based on yield index while providing the same protection to both suppliers and buyers. More information about EWMA sampling plan can be found in [17].…”
Section: Introductionmentioning
confidence: 99%
“…It must be remembered, however, that the superiority of the variables plan rests on the assumption of the underlying distribution of the measurements [6]. Whether the performance measure is single quality characteristic [7][8][9][10]15] or profile data [16,21] sampling schemes in the literature share two basic assumptions: the quality characteristic follows a normal distribution and data is independent. However, in some manufacturing processes, data is correlated or self-dependent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation